2016
DOI: 10.1523/eneuro.0275-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Population EEG Dynamics throughout Adulthood

Abstract: For decades, electroencephalography (EEG) has been a useful tool for investigating the neural mechanisms underlying human psychological processes. However, the amount of time needed to gather EEG data means that most laboratory studies use relatively small sample sizes. Using the Muse, a portable and wireless four-channel EEG headband, we obtained EEG recordings from 6029 subjects 18–88 years in age while they completed a category exemplar task followed by a meditation exercise. Here, we report age-related cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 47 publications
7
69
0
1
Order By: Relevance
“…There are reports suggesting either increases (Rossini et al, ) or decreases in delta/theta power with increasing age, both of which have been found to be associated with cognitive impairments (Finnigan & Robertson, ; Stomrud et al, ). Non‐linear relationships with age have also been suggested, indicating reversal of delta power from decreases to increases in later life (Gomez et al, ; Hashemi et al, ). Typically such alterations are accompanied by complementary changes in high‐frequency power (alpha/beta) describing the overall shift in toward either slowing or speeding with age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There are reports suggesting either increases (Rossini et al, ) or decreases in delta/theta power with increasing age, both of which have been found to be associated with cognitive impairments (Finnigan & Robertson, ; Stomrud et al, ). Non‐linear relationships with age have also been suggested, indicating reversal of delta power from decreases to increases in later life (Gomez et al, ; Hashemi et al, ). Typically such alterations are accompanied by complementary changes in high‐frequency power (alpha/beta) describing the overall shift in toward either slowing or speeding with age.…”
Section: Discussionsupporting
confidence: 90%
“…The findings related to spectral slowing in dementia are of particular importance because they appear in the direction opposite to what is typically seen with normal aging. Healthy elderly adults exhibit decreased low‐frequency power and increased high‐frequency power (Gomez, Perez‐Macias, Poza, Fernandez, & Hornero, ; Hashemi et al, ), indicating a shift toward faster oscillatory dynamics, contrasting with the patterns reported in dementia.…”
Section: Introductionmentioning
confidence: 99%
“…It is also not known how well the active electrodes that we used in this study preform in movement situations, and some research has shown that data of similar quality can be measured with electrodes with no active amplification (Debener et al, 2012;Zink et al, 2016). Finally, consumer grade EEG hardware is becoming increasingly sophisticated, and very affordable Bluetooth EEG systems have been shown to measure research quality EEG and ERP data (Krigolson, Williams, Norton, Hassall, & Colino,2017;Hashemi et al, 2016). We are also testing how these systems can be integrated into our experimental setup to further increase portability and minimize obtrusiveness of the equipment.…”
Section: Discussionmentioning
confidence: 99%
“…The peak frequency of alpha activity (i.e the frequency within the 8-12Hz, that has the maximal power) has been found to change across the life span, increasing from childhood to adulthood, and subsequently decreasing with age (Aurlien et al, 2004;Lindsley, 1939,Hashemi et al, 2016Bazanova & Vernon, 2014). There is evidence that the frequency of alpha activity is positively correlated to measures such as working performance (reviewed in Klimesch, 1999).…”
Section: Introductionmentioning
confidence: 99%